Hi I'm doing a project in math and seem to be stuck on one part.(adsbygoogle = window.adsbygoogle || []).push({});

I come to trying to solve this recursion equation given by....

f(x) = -f(x-1) + g(x) where g(x) is known.

Would anyone mind showing me how to go around solving for f(x)?

In this case i have g(x)=x[tex]^{2}[/tex] and f(0)=0 and f(1)=1

but will need to solve for any g(x) later on.

Thank You!

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Simple recursion

**Physics Forums | Science Articles, Homework Help, Discussion**